A systematic review of university students’ mental health in sub-Saharan Africa - Bokamoso Julius; Manish Putteeraj; Jhoti Somanah (Transformation in Higher Education, 2024)
The mental health of students in higher education is an increasing concern. Research indicates that university students are at a higher risk of poor mental health and wellbeing compared to the general population, which negatively impacts their studies. The main issue addressed in this study is the evident gap in mental health research dedicated to university students in sub-Saharan Africa (SSA). The purpose of this article is to review the literature on mental health of university students in SSA and to provide an overview of student mental health policy in educational institutions. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 recommendation was followed to objectively select and retain articles within the topic of interest for this systematic review. Findings indicate a significant gap in mental health research for university students in SSA. There is a need for higher education institutions to establish mental health empowerment policies and strategies. International examples, such as the University Mental Health Framework in Australia and the United Kingdom Universities Student Wellbeing Good Practice Guide, exist for benchmarking.